Simulasi Penggunaan Teman Bus Medan Berbasis Animasi 2 Dimensi - Amaliy, Soufa; Dafitri, Haida; Wulan, Nur (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2024)
Facilities and infrastructure are a crucial part of the development and construction of a region or country, one of which is public bus transport, which plays an important role in an efficient transport system. The transition from conventional to digital systems is not always easy for the community, especially in the city of Medan. Surveys have shown that people have difficulty using the Trans Metro Deli digital bus transport system to obtain information about bus routes and schedules, and to make cashless payments that were previously made in cash. To overcome this problem, a simulation video of its use was created based on 2-Dimensional animation using the Motion Graphic method with Adobe Flash CS6. Motion Graphic is a graphic design science that combines various elements such as illustration, typography, photography and animation to create dynamic and audiovisually appealing visuals. The output resulted in the form of a 2-Dimensional animation-based simulation video in the use of Trans Metro Deli bus transport using the Teman Bus application. The results of this research are expected to help the city of Medan face the challenges of transitioning from conventional transport to digital public transport, as well as increase public interest in using the service in the future.